EVALUASI PENERAPAN E-TOURISM: STUDI KASUS PENGAPLIKASIAN PLATFORM ONLINE BOOKING DINAS PARIWISATA DAERAH ISTIMEWA YOGYAKARTA - Danardono Widyapranoto (ABIS: Accounting and Business Information Systems Journal, 2019)
ABSTRACTThis research aimed at identifying and analyzing the e-tourism application managed by the Special Region of Yogyakarta Tourism Office (Dispar DIY). The research also aimed at finding out the reasons why DIY Tourism Office has not applied the online booking platform as a part of its service transformations. This research employed 7 dimensions in the TOE framework to optimize the e-tourism application using online booking platform. Those 7 dimensions are IT skills, IT infrastructure, top management support, organizational compatibility, coordination level, regulation, and competitive environment. The research results showed that the e-tourism application in DIY Tourism Office was carried out using website to share information and to promote tourism activities. Concerning the objectives, the service information provided by DIY Tourism Office was a one-way static interaction. Actually, the static services can be transformed into the dynamic ones by applying the online booking platform. However, the platform application was not listed as a priority program of DIY Tourism Office since there was no specific regulation or rule established to encourage the use of online reservation and booking service. On the other hand, making innovation in service provision was another challenge because the DIY Tourism Office management has not fully supported the priority program. As for the organizational level, human resources development at the DIY Tourism Office that is by assigning an employee who specializes in IT has not been well-executed. This should make a serious concern for the DIY Tourism Office in relation with its organizational management.